ECONOMIC ASSESSMENT OF PROSPECTS FOR MONITORING TELEVISION NEWS AND THE BLOGOSPHERE AS A TYPE OF BUSINESS ACTIVITY - Rexhepi, Burhan Reshat; Berisha, Burim Isa; Dauti, Bardhyl; Hajrizi, Edmond (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The primary goal of this study is to conduct a comprehensive economic evaluation of the prospects for monitoring television news and the blogosphere as entrepreneurial activities in Ukraine. Additionally, the study aims to assess the quality of media content and its social impact, focusing on the evolving role of television news and the blogosphere in influencing public opinion and consumer behavior. To achieve this, the study utilizes a combination of analytical methods, including comparative analysis, formalization, and synthesis, along with the development of a monitoring matrix to evaluate the content quality of both media channels. The results of the study indicate that both television news and the blogosphere have evolved beyond their traditional roles as sources of information and entertainment. These platforms now serve as powerful tools for marketing and social influence, with the blogosphere playing an increasingly significant role in consumer engagement and political discourse. The study also highlights the growing demand for monitoring services within this sphere, with implications for businesses and government agencies alike. In conclusion, the authors identify that monitoring television news and the blogosphere not only provides valuable insights into the social and economic impact of these media but also presents a promising avenue for entrepreneurial activity. The findings suggest that the development of a systematic monitoring algorithm could enhance the quality of information and improve user engagement across both platforms.